2019
DOI: 10.1016/j.isci.2019.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Adaptation to Electrochemical Perturbation in Planaria: A Molecular Analysis of Physiological Plasticity

Abstract: SummaryAnatomical homeostasis results from dynamic interactions between gene expression, physiology, and the external environment. Owing to its complexity, this cellular and organism-level phenotypic plasticity is still poorly understood. We establish planarian regeneration as a model for acquired tolerance to environments that alter endogenous physiology. Exposure to barium chloride (BaCl2) results in a rapid degeneration of anterior tissue in Dugesia japonica. Remarkably, continued exposure to fresh solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 127 publications
(148 reference statements)
0
34
0
Order By: Relevance
“…Could GRNs likewise exhibit history-dependent behavior that could help explain variability and be could be exploited to control their function by modulating the temporal sequence of inputs? Based on the remarkable flexibility observed at the anatomical and physiological levels ( Blackiston and Levin, 2013 ; Emmons-Bell et al., 2019 ; Levin, 2014 ; Schreier et al., 2017 ; Soen et al., 2015 ; Sullivan et al., 2016 ), and the conceptual similarity between GRNs and neural networks ( Sorek et al., 2013 ; Watson et al., 2010 , 2014 ), we first established a formalization of memory types for GRNs and implemented a suite of computational tests that reveal trainability in a given GRN ( Figures 2 and 3 ). We next created and tested thousands of 2-node and 3-node networks to identify minimal networks exhibiting each type of memory ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Could GRNs likewise exhibit history-dependent behavior that could help explain variability and be could be exploited to control their function by modulating the temporal sequence of inputs? Based on the remarkable flexibility observed at the anatomical and physiological levels ( Blackiston and Levin, 2013 ; Emmons-Bell et al., 2019 ; Levin, 2014 ; Schreier et al., 2017 ; Soen et al., 2015 ; Sullivan et al., 2016 ), and the conceptual similarity between GRNs and neural networks ( Sorek et al., 2013 ; Watson et al., 2010 , 2014 ), we first established a formalization of memory types for GRNs and implemented a suite of computational tests that reveal trainability in a given GRN ( Figures 2 and 3 ). We next created and tested thousands of 2-node and 3-node networks to identify minimal networks exhibiting each type of memory ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when planaria are exposed to barium, a nonspecific potassium channel blocker, their heads explode. Remarkably, they soon regenerate heads that are completely insensitive to barium [141]. Transcriptomic analysis revealed that relatively few genes out of the entire genome were regulated to enable the cells to resolve this physiological stressor using transcriptional effectors to change how ions and neurotransmitters are handled by the cells.…”
Section: Specific Conceptual Components Of the Tame Frameworkmentioning
confidence: 99%
“…This includes the transcriptional space of gene expression (B) here schematized for two genes, anatomical morphospace (C) here schematized for two traits, and physiological space (D) here schematized for two parameters. An example (E) of problem-solving is planaria, which placed in barium (causing their heads to explode due to general blockade of potassium channels) regenerate new heads that are barium-insensitive [141]. They solve this entirely novel (not primed by evolutionary experience with barium) stressor by a very efficient traversal in transcriptional space to rapidly up/down regulate a very small number of genes that allows them to conduct their physiology despite the essential K + flux blockade.…”
Section: Figure 2: the Axis Of Persuadabilitymentioning
confidence: 99%
“…6A). We have previously observed a similar adaptation of D. japonica to BaCl 2 which induces very rapid (within 3 days) head degeneration while AdOx-prompted head regression happens relatively slowly (within 10 days) [30]. We first hypothesized that adaptation to AdOx arises due to exposure to the inhibitor during head regeneration.…”
Section: Resultsmentioning
confidence: 96%